"That Little Bit of Time": Transition-to-Hospice Perspectives From Hospice Staff and Bereaved Family. Issue 1 (18th January 2022) - Cross, Sarah H; Ramkalawan, Janel R; Ring, Jackie F; Boucher, Nathan A
Abstract: Background and Objectives: Many patients lack understanding of hospice services and their preparation for the transition to hospice at home may be insufficient. This study explored how hospice admissions staff and caregivers of hospice patients perceive the hospice admission process and the transition to hospice at home. Research Design and Methods: We conducted in-depth, semistructured interviews with 2 subgroups: hospice admissions staff ( n = 15) and bereaved caregivers of former hospice patients ( n = 20). We performed a 3-coder descriptive content analysis. Results: There were 4 overall themes: (a) issues relating to the referring/prehospice provider, (b) issues relating to hospital discharge/care transition home, (c) issues relating to the first touch of hospice, and (d) the impact of coronavirus disease 2019 (COVID-19) on hospice admissions. Patients are often referred to hospice without clear prognostic understanding, at times placing staff in the uncomfortable position of breaking difficult news. Stigma may make patients and families fearful of enrolling in hospice, and misconceptions about hospice are common. Caregivers emphasize the need for increased attention to their emotional needs. Staff revealed the emotional challenges they experience conducting admissions. Both staff and caregivers indicate that the transition to hospice is often emotionally and logistically burdensome, especially when discharging home from the hospital. Both subgroups report insufficient caregiver preparation for taking care of a dying patient at home, particularly regarding medication management. COVID-19 created challenges yet prompted innovative changes to hospice admission processes. Discussion and Implications: Findings demonstrate a need to improve the hospice admissions process, better supporting terminally ill patients and their families.